Morphological Functions of Derivational Suffixes in BBC News: Earth Edition - Pratama, I Gede Angga; Ni Putu Cahyani Putri Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This research focused on analyzing class-changing derivational suffixes found in the article of BBC News: Earth Edition. In this research, class-changing derivational suffixes from BBC News: Earth Edition stories were analyzed using a qualitative method. The note-taking method applied in collecting data for this research. The data collection involved reading five selected articles from the BBC News: Earth Edition website, noting relevant information, and classifying the functions of derivational suffixes. This study applied the theory proposed by McCarthy (2002) in analyzing the morphological function of derivational suffixes in each word. By highlights how different suffixes modify the root word and how these modifications fit into broader morphological patterns, it helps in identifying systematic relationships between suffixes and the meanings they produce. Formal and informal methods were applied in this study in presenting the data. This study identified four functions of class-changing derivational suffixes, namely adverb derived from adjective (32%), adjective derived from noun (11%), verb derived from noun (0%), noun derived from verb (57%). The findings indicated that nouns derived from verbs were more frequently found in the online news stories of BBC News: Earth Edition.